Maintenance and Growth Requirements in Male Dorper × Santa Ines Lambs - Mendes, Marcilio S.; Souza, Jocely G.; Herbster, Caio Julio L.; Brito Neto, Antonio S.; Silva, Luciano P.; Rodrigues, João Paulo P.; Marcondes, Marcos I.; Oliveira, Ronaldo L.; Bezerra, Leilson R.; Pereira, Elzania S. (Frontiers in Veterinary Science, 2021)
The aim of this study was to estimate the energy and protein requirements for maintenance and growth of lambs. A total of 35 crossbreed Dorper x Santa Ines lambs (31 ± 1.28 kg of initial body weight (BW) and 4-months old) were distributed in a completely randomized design with three treatments groups (ad libitum, 30% and 60% of feed restriction). Five lambs were slaughtered at the beginning of the experimental trial as a reference group to estimate the initial empty BW (EBW) and body composition. When the animals of the ad libitum treatment reached a BW average of 47.2 kg, at day 84 of trial, all lambs were slaughtered. The feed restriction promoted reduction in body fat (P < 0.001) and energy concentration (P < 0.001), while protein showed a quadratic response (P = 0.05). The equations obtained to NEg and NPg requirements were 0.2984 × EBW0.75 × EBWG0.8069 and 248.617 × EBW-0.15546, respectively. The net energy (NEm) and protein (NPm) for maintenance were 71.00 kcal/kg EBW0.75/day and 1.76 g/kg EBW0.75/day, respectively. In conclusion, the NEg and NPg requirement for lambs with 30 kg of BW and 200 g of average daily gain (ADG) were 0.736 Mcal/day and 24.38 g/day, respectively. Our findings indicate that the NEm for crossbreed Dorper x Santa Ines lambs is similar to those recommended by the international committees, however we support the hypothesis the requirements for gain are lower.